HBR Guide to: Making Every Meeting Matter - Harvard Business Review (Harvard Business Review Press, 2016)
Make every minute count. Your calendar is full, and yet your meetings don t always seem to advance your work. Problems often arise with unrealistic or vague agendas, off-track conversations, tuned-out participants who don t know why they re there, and follow-up notes that no one readsor acts on. Meetings can feel like a waste of time. But when you invest a little energy in preparing yourself and your participants, you ll stay focused, solve problems, gain consensus, and leave each meeting ready to take action. With input from over 20 experts combined with useful checklists, sample agendas, and follow-up memos, the HBR Guide to Making Every Meeting Matter will teach you how to: Set and communicate your meeting s purpose Invite the right people Prepare an achievable agenda Moderate a lively conversation Regain control of a wayward meeting Ensure follow-through without babysitting or haranguing Arm yourself with the advice you need to succeed on the job, from a source you trust. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges."